(untitled) (Swiss Medical Weekly, 2021)
AIMS OF THE STUDY Anticoagulation of patients with screen-detected atrial fibrillation may prevent ischaemic strokes. The STAR-FIB study programme aims to determine the age- and sex-specific prevalence of silent atrial fibrillation and to develop a clinical prediction model to identify patients at risk of undiagnosed atrial fibrillation in a hospitalised patient population. METHODS The STAR-FIB study programme includes a prospective cohort study and a case-control study of hospitalised patients aged 65–84 years, evenly distributed for both age and sex. We recruited 795 patients without atrial fibrillation for the cohort study (49.2% females; median age 74.8 years). All patients had three serial 7-day Holter ECGs to screen for silent atrial fibrillation. The primary endpoint will be any episode of atrial fibrillation or atrial flutter of ≥30 seconds duration. The age- and sex-specific prevalence of newly diagnosed atrial fibrillation will be estimated. For the case-control study, 120 patients with paroxysmal atrial fibrillation were recruited as cases (41.7% females; median age 74.6 years); controls will be randomly selected from the cohort study in a 2:1 ratio. All participants in the cohort study and all cases were prospectively evaluated including clinical, laboratory, echocardiographic and electrical parameters. A clinical prediction model for undiagnosed atrial fibrillation will be derived in the case-control study and externally validated in the cohort study. CONCLUSIONS The STAR-FIB study programme will estimate the age- and sex-specific prevalence of silent atrial fibrillation in a hospitalised patient population, and develop and validate a clinical prediction model to identify patients at risk of silent atrial fibrillation.